DEVELOPMENT OF INFORMATION MANAGEMENT SYSTEM FOR AKADEMI KOMUNITAS PRESIDENT - Zhafran Rifandi; Ronny Juwono (President University, 2022)
The Akademi Komunitas President is an educationalinstitution under the auspices of the president university, thePresident Community Academy provides education with diplomas2 and 3 and there are also LPK programs or job traininginstitutions for people outside the president Community Academywho wish to receive job training courses. However, the President'sCommunity Academy does not have an information managementsystem that supports administrative, academic and informationsharing activities, this causes the workload to be high and workefficiency to be low. To solve this problem, I propose this finalproject to create an information management system for thePresident's Community Academy.